Optimal relay coordination for grid connected variable size DG - Purwar E.; Vishwakarma D.N.; Singh S.P. (My University, 2025)
Distributed Generators (DGs) are gaining popularity due to power industry deregulation and unpredictable growing loads. For every future increment in DG capacity, the relay settings need to be changed. This paper investigates how varying capacity of DG at a bus affects relay coordination. It proposes a new formulation of optimal relay coordination in the presence of variable size DG connected with grid. The proposed study yields one group of optimal relay settings that are feasible for all possible future DG installations. The optimization problem is solved using built in function fmincon in the Matlab optimization Toolbox. The performance of proposed approach is tested on a 11Kv, 5 feeder radial distribution network using Matlab. The results verified that the proposed relay coordination formulation is able to accurately coordinate the primary and backup relays irrespective of the size of DG within the specified upper limit for a given location. © 2016 IEEE.